Legal aspects of the definition «Сompromise of the personal key of digital signature» - Корнейко, Олександр Васильович; Костенко, Олексій Володимирович (Ukrainian Information Security Research Journal, 2020)
The article is devoted to the definition of “compromise of the personal key of digital signature” in the context of law science. It is shown that although in the scientific and technical literature the problem of compromising the private key of digital signature and its types is presented quite fully, in the legal literature there is no single interpretation of this definition and the legal consequences of compromise. Examples of these definitions in various regulations of Ukraine and other countries are given. It is shown why the resolution of the legal uncertainty of the definition “compromise of digital signature private key” and timely response of the right to digital risks is an urgent problem of legal science. It is shown how the lack of a list of basic signs of personal key compromise in the legislation creates ambiguity in the interpretation by law enforcement agencies, courts and the bar of signs of crimes committed with the use of electronic signatures. It is shown how the existing problems cause distrust of the legislation in the field of electronic signatures, doubts about the reliability of electronic signatures and their private keys, the integrity and reliability of electronic documents signed by them. Examples of this legal problem in the context of relevant court decisions are given. Examples of explicit and implicit compromise of a private key of digital signature and their limits, as well as the legal consequences of compromise are given. Based on the results of the research, appropriate definitions are proposed, which are recommended to be included in the existing version of the Law of Ukraine “On electronic trust services”. The authors conclude that this will contribute to: the legal regulation of public relations related to the use of electronic signatures; clear classification of crimes and offenses committed using an electronic signature personal key; increase confidence in the reliability of electronic signatures and electronic documents signed by them, agreements and contracts concluded in electronic form; will stimulate the development of cross-border e-commerce and services.